Tales of Migration without Wage Differentials: Individual, Family, and Community Contexts - Oded Stark (Institutions and Economic Development, 2003)
By means of examples that pertain to individual, family, and community contexts, it is shown that migration between locations is compatible with a zero expected net earnings differential between locations. The examples give rise to testable predictions that differ sharply from the predictions that emanate from a standard postulate of earnings differential.
Keywords: D01; D13; D14; D15; J12; J26; J31; J61; O10; O15; R23; Z13; 330; Individual context; Family context; Community context; A zero expected net earnings differential between regions; Testable predictions; Limitations of conventional policies; New policy instruments; Preference formation; Migration preferences; Marriage and migration; Relative deprivation; Individual and community decision-making